PENDAMPINGAN BELAJAR DARI RUMAH (BDR) SISWA MTS AL-MUDDATSIRIYAH PADA MASA PANDEMI COVID 19 - Syafruddin Syafruddin; Wiwi Noviati; Indah Dwi Lestari; Eryuni Ramdhayani; Ana Merdekawaty; Sri Sugiarto (Politeknik Negeri Sriwijaya, 2021)
The spread of Covid 19 to date has shifted the learning process that should have taken place face-to-face to online learning. Learning from home is one solution in carrying out learning during this pandemic to avoid the increasing spread of Covid 19. Interactive learning media is very necessary in supporting the teaching and learning process in schools, especially in online learning. This dedication is motivated by a problem, namely students tend to be bored in learning from home because teachers are not optimal in using learning media that should be needed in online learning. The purpose of this community service is to provide online learning assistance to students by utilizing interactive learning videos in the new order. The method used in this study is divided into three stages, namely the preparation stage, the implementation stage and the evaluation stage. Based on the implementation of service activities that have been carried out, it can be concluded that this activity received a positive response from students, it can be seen from the enthusiasm for receiving the subject matter presented by all presenters, because there were new experiences gained by students. In addition, the delivery of material is not only equated verbally but also utilizes learning media in the form of interactive videos so that the material presented is more interesting for students.